Erythrocyte membrane-cloaked polymeric nanoparticles for controlled drug loading and release. (August 2013) - Aryal, Santosh; Hu, Che-Ming J; Fang, Ronnie H; Dehaini, Diana; Carpenter, Cody; Zhang, Dong-Er; Zhang, Liangfang
Aim: Polymeric nanoparticles (NPs) cloaked by red blood cell membrane (RBCm) confer the combined advantage of both long circulation lifetime and controlled drug release. The authors carried out studies to gain a better understanding of the drug loading, drug-release kinetics and cell-based efficacy of RBCm-cloaked NPs.Materials & methods: Two strategies for loading doxorubicin into the RBCm-cloaked NPs were compared: physical encapsulation and chemical conjugation. In vitro efficacy was examined using the acute myeloid leukemia cell line, Kasumi-1.Results: It was found that the chemical conjugation strategy resulted in a more sustained drug release profile, and that the RBCm cloak provided a barrier, retarding the outward diffusion of encapsulated drug molecules. It was also demonstrated that RBCm-cloaked NPs exhibit higher toxicity in comparison with free doxorubicin.Conclusion: These results indicate that the RBCm-cloaked NPs hold great promise to become a valuable drug-delivery platform for the treatment of various diseases such as blood cancers. Original submitted 27 February 2012; Revised submitted 27 August 2012; Published online 14 February 2013